2010
DOI: 10.2460/ajvr.71.6.610
|View full text |Cite
|
Sign up to set email alerts
|

Ease of oral administration and owner-perceived acceptability of triglyceride oil, dissolving thin film strip, and gelatin capsule formulations to healthy cats

Abstract: Daily ease of administration on 11 of 14 days and overall owner-perceived acceptability to cats were scored significantly higher for film strips and MCT oil, compared with scores for gelatin capsules. Overall acceptability to owners followed a similar pattern; however, the differences were not significant. Dissolving thin film strip or MCT oil vehicles may allow for easier PO administration of medication to cats than does administration of gelatin capsules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 4 publications
(4 reference statements)
0
5
0
Order By: Relevance
“…Administration of AM agents used for dogs was principally by oral tablet (81 per cent), whereas the majority of AM agents for cats were administered via the injectable method (55 per cent). This likely reflects general differences in methods of administering medicines between the species, with oral tablets being perceived as more difficult to effectively administer in cats (Traas and others 2010). Dogs received proportionally more aminopenicillin types (54 per cent v 46 per cent) and nitromidazoles (11 per cent v 5 per cent) than cats.…”
Section: Discussionmentioning
confidence: 99%
“…Administration of AM agents used for dogs was principally by oral tablet (81 per cent), whereas the majority of AM agents for cats were administered via the injectable method (55 per cent). This likely reflects general differences in methods of administering medicines between the species, with oral tablets being perceived as more difficult to effectively administer in cats (Traas and others 2010). Dogs received proportionally more aminopenicillin types (54 per cent v 46 per cent) and nitromidazoles (11 per cent v 5 per cent) than cats.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, several field trials have been conducted in the last few years in cats (Litster and others 2007, Gunew and others 2008, Traas and others 2010, Morton and others 2011, Khor and others 2012). In these studies, the owners evaluated the acceptability of pharmaceutical drugs via questionnaires, a rating of the ease of administration on a 10‐cm visual analogue scale, a rating of overall acceptability of formulations from their own perspective and their overall perception of acceptability to their cat, or via the ease of administration of the tested formulations.…”
Section: Discussionmentioning
confidence: 99%
“…It was evaluated the overall owner-perceived acceptability and the easiness administration of an orodispersible film compared with gelatin capsules in cats. Although there were no significant differences in the general acceptability of the owners, it was shown that the orodispersible films facilitated significantly the administration of the medication [149,150]. Currently, few companies have developed oral films applied to this segment, and the available products are scarce and limited to OTC products based on blends of herbal extracts [151,152].…”
Section: Market Outlookmentioning
confidence: 99%